Effect of bioaugmentation on start-up phase of anaerobic digestionat high organic loading rate - Cheng, Xingyu; Zheng, Guoxiang; Hu, Zhiyuan; Yan, Miao; Zhen, Feng; Li, Ying; Li, Jiachen; Dong, Taili; Chen, Li; Sun, Yongming (International Journal of Agricultural and Biological Engineering, 2025)
In order to enhance the start-up of anaerobic digestion (AD), the propionate-degrading methanogenic cultures were introduced to AD of food waste at a high organic loading rate (OLR) of 3.0 g VS/L∙d in this study, and the efficiency of different bioaugmentation strategies were investigated. The results demonstrated that bioaugmentation significantly improved the start-up efficiency and enhanced the methane production. Specifically, higher dosage and frequency of bioaugmentation had a positive effect on the performance of the AD reactors. Among three bioaugmented reactors, the reactor with a bioaugmentation strategy of 0.675 g VS/L of bioaugmentation seed added every 5 d during the first hydraulic retention time (HRT) performed the best and remained relatively stable for the next three HRTs without bioaugmentation. The 16S rRNA gene sequencing analysis revealed that Methanothrix predominated in bioaugmented reactors. A large proportion of Methanothrix accompanied by a small proportion of Methanospirillum played a key role in volatile fatty acid degradation and contributed to the successful start-up and long-term stability of AD at a high OLR. These findings suggest that bioaugmentation with methangenic consortium is a promising strategy to boost the AD process at high OLRs and achieve higher treatment capacity of food waste. Keywords: high organic loading rate, anaerobic digestion, bioaugmentation, propionate degradation, Methanothrix DOI: 10.25165/j.ijabe.20251801.9026 Citation: Cheng X Y, Zheng G X, Hu Z Y, Yan M, Zhen F, Li Y, et al. Effect of bioaugmentation on start-up phase of anaerobic digestionat high organic loading rate. Int J Agric & Biol Eng, 2025; 18(1): 292–298.